Physicochemical and thermal properties of durian seed flour from three varieties of durian native of Sabah - Siti Faridah Mohd Amin; Nur Atikah, M.R.L.; Lee, Jau Shya; Hasmadi Mamat; Mohd. Rosni Sulaiman; Wolyna Pindi; Noorakmar Ab. Wahab (Rynnye Lyan Resources, 2021)
This study was aimed at assessing the physicochemical and thermal properties of flour, acquired from the seeds of three native Sabah durian species. The three-durian species concerned are the Dalit, Sukang and Pulu. Flour deriving from the seeds of the dalit (DDSF), sukang (DSSF) and pulu (DPSF) durian species, were put through a physicochemical, pasting and thermal characteristics assessment process. The protein content in flours, derived from the seeds of durian native to Sabah, demonstrated a high capacity for the absorption of both water (r = -0.855, p<0.01), and oil (r = 0.921, p<0.01). DPSF, which holds the most protein content at 6.92%, demonstrated the lowest water absorption capacity, and greatest oil absorption capacity (p<0.05). Moreover, DPSF was observed to have the lowest swelling power, solubility and peak viscosity (p<0.05). In terms of pasting temperature, no outstanding disparities were detected between the three durian seed flours (p>0.05), but they were considered to have high pasting temperatures. The lowest setback viscosity (p<0.05) displayed by DPSF, is an indication that the following gelatinization, will quickly dissolve. Additionally, the enthalpy ΔH of DPSF revealed as 0.29 J/g (p<0.05) is deemed significantly low. This undertaking delves into the physicochemical and thermal characteristics of durian seed flour, to its use as composite flour.